Efficiency of the Conventional DNA Extraction Method in Polymerase Chain Reaction (PCR) Detection of Porcine DNA in Selected Raw and Cooked Meat Products - Zaliha, Suadi (Universiti Malaysia Sarawak, 2022)
The rapid development of technology and the abundance of various resources in the food industries have resulted in easy access to various types of meat-based food products to meet the demands of today's customers. Today, halal food is no more a mere religious obligation but has moved to become an alternative benchmark for safety, hygiene, and quality assurance for the daily consumption of Muslims and non-Muslims. Animal species used as raw materials in industrial food production and food products should always be identified by food safety and quality control laboratories. High-quality DNA is a prerequisite for successful species identification using PCR-based techniques; therefore, selecting the right DNA extraction method is crucial. Some studies found that the conventional phenol/chloroform extraction method is reliable and cost-effective in extracting DNA from meat products despite being time-consuming and hazardous to health; however, these chemicals are unlikely to cause harm when used and handled correctly. There are reports comparing DNA extraction protocols from meat that focus on seafood, canned food, and processed meat. However, no comparison of the efficiency of DNA extraction methods from ready-to-eat or cooked meat items, primarily from chicken, beef, and pig species, has been reported, especially in Sarawak. Hence, this study aimed to evaluate the efficiency and suitability for amplification of porcine DNA in selected processed and home-cooked meat products using the conventional phenol/chloroform/isoamyl alcohol (PCIA) DNA extraction method and comparing it to a commercially available kit. A UV-Vis spectrophotometer was used to assess the quantity and quality of the DNA extracts. PCR was carried out with species-specific primers targeting the mitochondrial DNA cytochrome b gene of chicken (227-bp), beef (274-bp), and pork (398-bp) to verify the PCR assay on these DNA extracts. The visualization of pork DNA on 2% agarose gel was able to detect pork contamination in raw meat mixtures up to 1%. The presence of pork in chicken and beef was indicated with a specific 398-bp DNA band. Out of 23 processed and home-cooked samples analyzed, only one failed to produce a band. Both extraction methods failed to develop a band from sample CF5 (pork stew with fermented vegetables). In cooked sample CF15 (steamed egg rolls with pork), only a chicken band was detected even though both chicken and pork bands were detected in its raw processed meat products PF17 (egg rolls with pork). Two jerky samples labeled as “Mini Chicken” contained pork only, and no chicken band was detected. In this study, the performance of the PCIA method was found to be equal to the commercial kit. Hence, the PCIA method can be recommended as a cost-effective and good alternative to more expensive extraction kits for detecting pork DNA in processed and home-cooked meat products. This research’s favorable outcome is substantial for species identification in food products, specifically for halal analysis. Commercial kits are undeniably simple to use and can aid in producing high-quality DNA in large quantities. They are, however, an expensive option, particularly for developing countries. There is always the possibility that a product will be discontinued or that these manufacturers will fail to meet any of the accreditation criteria.